Costo-beneficio del uso de fundas biodegradables e implementacion de las normas ambientales caso de estudio: supermercados de la ciudad de Quevedo provincia de los Ríos - Cruz Álava, Glenda Gisselle (2015)
This research was conducted in the city of Quevedo, and was directed towards the supermarkets of the city. In order to meet the cost-benefit each Supermarket obtained by using covers and / biodegradable packaging in the sale of its products, taking into account environmental campaigns being carried out by the Ministry of Environment. Another point on which this work has been done this is due to the popularity of common plastic bags which are made from polyethylene, and are consumed in large quantities because of its convenience when making purchases for the home, and then the same can be reused for garbage disposal. But even though these cases are so useful in daily life, they are making an impact on the ecosystem due to its slow decomposition which according to studies is hundreds of years, and this makes the environment to produce adverse effects on habitat the wildlife, or humans. That is why today is being awareness to this problem affecting our flora and fauna, and of course the health of people are already several environmental campaigns that are being provided to people to stop this impact on the environment. Since the Constitution of the Republic, the National Plan for Good Living, the Environmental Management Act says that everyone is entitled to live in a healthy environment. One strategy is the use of biodegradable bags, they like common plastics are made from petroleum derivatives (polyethylene) with the difference of the special additive is added at the time of manufacture which will allow the sleeves They degrade quickly and this favors the environment.